Analisis Perbedaan Kualitas Pelayanan Listrik Pascabayar dan Listrik Prabayar terhadap Kepuasan Pelanggan Pada PT PLN (Persero) Area Ciputat - rasyida leila ramadlana; mukhamad najib (Jurnal Manajemen dan Organisasi, 2016)
PT PLN (Persero) is a state-owned enterprise (SOE) managing all aspects of electricity in Indonesia for 44 years, works to increase the quality of life and customer satisfaction oriented. The purpose of this research is to determine the level of interest and level of satisfaction on postpaid and prepaid electricity, relationship between characteristic and customer satisfaction, and customer satisfaction difference to the quality of service. The method of analysis used is descriptive analysis, Importance Performance Analysis (IPA), Customer Satisfaction Index (CSI), Chi-squared test and T-test. The results showed that the attributes contained in quadrant A of Importance of Performance Matrix need to be improved so that customer satisfaction increase, the CSI value of postpaid and prepaid electricity have been satisfying customers. The result of chi-square test suggests that there is correlation between sex and customer satisfaction of prepaid electricity customers and the T-test result suggests that prepaid electricity customer satisfaction is higher than postpaid electricity customer satisfaction.